128k views
2 votes
Simplify (3x^2-4x+1)-(5x^2-2x+1).

2 Answers

5 votes

Answer:


\boxed{\bold{-2x^2-2x}}

Step By Step Explanation:

Remove Parenthesis: (a) = a

=
\bold{3x^2-4x+1-\left(5x^2-2x+1\right)}


\bold{-\left(5x^2-2x+1\right): \ -5x^2+2x-1}

=
\bold{3x^2-4x+1-5x^2+2x-1}

Simplify
\bold{3x^2-4x+1-5x^2+2x-1}

=
\bold{-2x^2-2x}

━ Mordancy ━

User Daren
by
6.0k points
6 votes

Answer:

-2x^2 -2x

Explanation:

if you need an explanation, message me, and i will post the picture of my work

User Sonstabo
by
6.5k points